Natural gas in Iraq between burning and licensing rounds - زيارة, رحيم حسوني; عزت, ثائر محي الدين (Journal of Economics and Administrative Sciences, 2018)
The research aims to shed light on the importance of Natural gas as a National wealth is not being used optimally to be a financial resource is important to Iraq in addition to Oil, as well as could be used as an important Source of Energy, instead of burning gas is a waste of wealth and Contribute to the contamination of the environment. Research Reviews the importance of Natural gas, where is currently about a quarter of global energy consumption. Then deals with the reality of the gas industry in Iraq and winning because of the volume of waste incineration, which reached a rate (45%) of the gas Associated with oil, where Iraq is fourth globally in Terms of the amount of gas Burned. Finally, this paper discusses the future of natural gas in Iraq through the Third Round of licenses and gas project which aimed to the south Increase the Proportion of gas exploitation in the future